Crayfish hematopoietic tissue cells but not hemocytes are permissive for white spot syndrome virus replication. Issue 1 (March 2015) - Wu, Junjun; Li, Fang; Huang, Jiajun; Xu, Limei; Yang, Feng
Abstract Hemocytes are the major immune cells of crustaceans which are believed to be essential for the pathogenesis of white spot syndrome virus (WSSV) infection. Crayfish hemocytes and hematopoietic tissue (HPT) cells have been found to be susceptible to WSSV infection, but the procedure of WSSV infection to both cell types has not yet been carefully investigated. In this study, we analyzed the infection and proliferation of WSSV in crayfish hemocytes as well as HPT cells in detail through transmission electronic microscopy (TEM). The results showed that WSSV could enter both hemocytes and HPT cells through endocytosis, but the production of progeny virus was only achieved in HPT cells. Further investigation demonstrated that although WSSV could transcribe its genes in both cell types, viral genome replication and structural protein expression were unsuccessful in hemocytes, which may be responsible for the failure of progeny production. Therefore, we propose that both hemocytes and HPT cells are susceptible to WSSV infection but only HPT cells are permissive to WSSV replication. These findings will extend our knowledge of the interaction between WSSV and the host immune system.